(untitled) (UNIHumanitas, 2013)
As a summary of this scientific article, I will now present two quotes from two eminent researchers from the Republic of Paraguay who have read and supported the thesis and the scientific article in question. “There is a problem with some disciplines, which, without the arguments or experimental possibilities that physics and, to a lesser extent, classical biology provide, is that they wish to follow the methodologies of these disciplines, when their own are not susceptible to being studied in depth in this way, and I agree that this reduces the possibility of scientific progress, because it enters a closed circle. Kuhn’s classical science, as you mention, also works in a closed circle as long as it is ordinary science and only changes when there are revolutions, which are very sporadic. This criticism was made by Sokal and Bricmont, but it was not understood by the humanists, that the scientific methods of some disciplines should not be used in others, which are very different, although the limits between one and the other may not be precise. I have a book written by a psychologist researcher, Dr. Kagan, called The Three Cultures. It is a little difficult for me. There is a lot of language from the area of ​​clinical and experimental psychology. It tries to distinguish, but with a continuous spectrum vision, between the natural sciences, the social sciences and the humanities, those three cultures. Hugs.” (Dr. Antonio Cubilla. November 1, 2012). “I have read carefully the conclusions that you have arrived at after subjecting the thesis books that you mention in the text to a deep and detailed discursive deconstruction. In fact, the way in which you outlined and carried out your research strategy allowed you to identify and enumerate these imponderables, contradictions, superpositions and theoretical proposals that are quite exotic in a context where the surrounding reality cries out for epistemological adaptations and transfers that give way to sincere and realistic approaches and proposals. Otherwise, research floats in the sterile void of that which “wants to be” by “being another.” The fact of putting on the table a reality that yields results that are not very encouraging in relation to the “way” in which we do research is a very important step in order to discuss and choose policies tending to the consolidation of strategies that root new “meanings” in scientific work. From now on, your research should serve to review the moment prior to the writing of the theses, the academic substrate that makes possible the confusions that you have identified. Your thesis gives rise to us reviewing and criticizing the “curriculum,” the backbone of the entire educational system. I encourage you to continue working. May these conclusions not remain trapped in bound pages, but rather may they travel through classrooms and from there promote “changes” in order to favor research where imagination is not constrained by the limits of statistics and proper and appropriate realities are not mutilated by foreign theories. “Let what is useful serve to increase solidarity and in this way, the research of human beings contribute to making us more human in order to feel free, and in equality, assume ourselves liberated.” (Dr. José Manuel Silvero Arévalos. November 8, 2012). “It really is an interesting work that tries to bring to light what is hidden, what is taken for granted and that, as you say, greatly influences scientific progress and the updating in this case of the field of clinical psychology.” (Prof. Dr. Antonio Miñán Espigares, Granada, Spain. November 8, 2012).